The Relationship Between Parents As Companions And Student Learning Motivation In PAI - Zaelani. AB (At-Tarbiyat, 2024)
This research aims to determine parental assistance in learning activities, the level of student learning motivation, as well as the positive and significant relationship between parents as companions for learning activities and student learning motivation in PAI subjects. The research method used is a quantitative method with a correlational research type. Hypothesis testing is carried out using the product moment correlation formula and strengthened using the t-test formula. Based on the results of data analysis, it can be seen that: (1) Parents of students in assisting their children's learning activities are included in the good category as evidenced by the average score of the questionnaire results of 66.53 (2) The level of student learning motivation in class VII PAI subjects at SMP Muhammadiyah 4, Tangerang City, it is included in the high category, as evidenced by the average score of 71.33 (3). There is a positive and significant relationship between parents as companions for learning activities and students' learning motivation in PAI subjects. The contribution of parents in learning activities to student learning motivation is 22.6% and the remaining 77.4% is influenced by other variables outside this research.